Different early and late processing of emotion-label words and emotion-laden words in a second language: An ERP study. (July 2020) - Zhang, Juan; Wu, Chenggang; Yuan, Zhen; Meng, Yaxuan
Although increasing literature has suggested that emotion-label words (e.g., anger, delight) and emotion-laden words (e.g., thief, bride) were processed differently in native language (L1), there was a lack of neuroimaging evidence showing such differences in second language (L2). The current study compared the cortical responses to emotion-label words and emotion-laden words in L2 using event-related potentials (ERPs) technique. Sixteen Chinese–English bilingual college students were asked to finish a lexical decision task with their brain activations recorded. Overall, emotion-label words and emotion-laden words showed diverse processing characteristics. Specifically, such differences were evidenced by the results that (1) larger N170 was elicited by negative emotion-label words than by negative emotion-laden words while positive emotion-laden words evoked larger N170 than positive emotion-label words at occipito-temporal sites, and (2) emotion-laden words evoked larger Late Positive Complex (LPC) than emotion-label words at parietal sites over the right hemisphere. The implication of the current findings was also discussed.